What About Affected Family Members of Disordered Gamblers During the COVID-19 Pandemic? A Study in Italy During the Lockdown Restrictions - Donati, Maria Anna; Capitanucci, Daniela; Beccari, Carola; Smaniotto, Roberta; Quadrelli, Eleonora; Casini, Alfredo; Primi, Caterina (Frontiers in Psychology, 2022)
Although some studies have been conducted on gambling behaviour in the general population or in clinical samples during the COVID-19 pandemic, less attention has been focused on Affected Family Members (AFMs) of disordered gamblers. To fill this gap, this study investigated the psychological state of disordered gamblers’ AFMs during the COVID-19 lockdown in Italy, the European country first affected by the virus and with the largest gambling market. We were interested in understanding if the unavailability of most land-based gambling offerings during the lockdown created a sense of relief in AFMs. We also compared the quality of family relationships and emotional state during the lockdown of AFMs with those of their relative with Gambling Disorder (GD). Participants were 53 disordered gamblers’ AFMs (77% female; mean age = 50.28). For 42 out of the 53 AFMs, we also recruited their relative with GD (86% male; mean age = 48.98). A semi-structured telephone interview was developed. Although AFMs reported a general interruption of the relative’s gambling behaviour and a general sense of relief for the closure of gambling activities, accompanied by the perception of good family relationships, AFMs still felt tired, worried and apprehensive and perceived more fear, stress and anxiety than before the lockdown. A large proportion of AFMs engaged in potentially addictive behaviours, especially TV, mobile phone and Internet use, which increased in frequency compared to before the pandemic. They still perceived some gambling-related problematic behaviours from their relative and put in place coping strategies to manage the gambling problem. Even if they had a general positive orientation toward the future, they experienced fear when thinking about the reopening of gambling opportunities at the end of the lockdown. Compared to their relatives with GD, AFMs appeared more prone to perceiving a general negative state and a worsening of it from before the lockdown. Overall, this study shows that disordered gambling’s AFMs can be considered as a particularly at-risk group who deserves focused clinical attention even during gambling closures related to pandemic lockdown.